Effect of a 6-week yoga intervention on swing mechanics during the golf swing: a feasibility study - Sorbie, G. S.; Low, C.; Richardson, A. K. (International Journal of Performance Analysis in Sport, 2019)
Recent evidence suggests that participating in physical conditioning programmes can improve golf performance; however, the effectiveness of a yoga intervention is yet to be investigated. The aim of the current study was to investigate the effectiveness of a 6-week yoga intervention on golf swing mechanics. Ten male golfers participated in the laboratory-based study. Golf swing mechanics were collected from two testing sessions, before and after the 6-week yoga intervention, using the Vicon motion capture system. Following the 6-week yoga intervention, significant changes were observed between the yoga and control group in X-Factor (P = 0.05) and a medium effect (d = 0.50) observed. No significant changes (P > 0.05) and no effect (d < 0.20) were observed in the X-Factor stretch. Significant changes (P = 0.05) and a medium effect (d > 0.50) were observed for the pelvis rotations following the yoga intervention; however, no differences were observed in torso rotations or hand velocities (P > 0.05). The findings of this feasibility study suggest that yoga may be a promising intervention in helping to improve golf swing mechanics; however, future research is required to confirm the effect of the use of yoga during the golf swing due to the sample size.